2017
DOI: 10.1177/0022219417708171
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of First-Grade Writing Profiles and Their Relationship to Compositional Quality

Abstract: To help all students meet the writing expectations of the Common Core State Standards, researchers need a deeper understanding of the characteristics of struggling writers. The purpose of this study was to explore the writing profiles of students including those who have or are at risk for writing disabilities. First-grade students ( N = 391) were assessed at the end of the school year using three writing assessments (spelling, sentence writing fluency, writing achievement). The researchers used latent profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
(77 reference statements)
1
23
0
4
Order By: Relevance
“…The observational data with this sample of teachers have been described in greater detail in a previous publication on the nature of first-grade writing instruction (Coker et al, 2016). Relationships among spring writing assessments with this sample of students have also been reported (Coker, Ritchey, Uribe-Zarain, & Jennings, 2017). However, in this study we present a new analysis of fall student assessments and spring reading outcomes that have not been published elsewhere.…”
Section: Methodsmentioning
confidence: 90%
“…The observational data with this sample of teachers have been described in greater detail in a previous publication on the nature of first-grade writing instruction (Coker et al, 2016). Relationships among spring writing assessments with this sample of students have also been reported (Coker, Ritchey, Uribe-Zarain, & Jennings, 2017). However, in this study we present a new analysis of fall student assessments and spring reading outcomes that have not been published elsewhere.…”
Section: Methodsmentioning
confidence: 90%
“…Written composition has been evaluated in multiple ways (e.g., Kim et al, 2017; Swartz et al, 1999), including writing quality, writing productivity, correctness in writing, spelling and conventions, vocabulary, and syntactic complexity. Studies found that these different dimensions of written composition are related but dissociable (Coker et al, 2018; Kim et al, 2014; Kim, Al Otaiba et al, 2015; Puranik et al, 2008; Wagner et al, 2011). Writing quality is the most widely evaluated dimension of written composition, is arguably the most important dimension, and typically includes coherence and quality of ideas, and use of language (vocabulary and sentence structure; e.g., Coker et al, 2018; Graham et al, 2002; Hooper et al, 2002; Kim et al, 2015; Olinghouse, 2008).…”
Section: Direct and Indirect Effects Model Of Writingmentioning
confidence: 99%
“…Studies found that these different dimensions of written composition are related but dissociable (Coker et al, 2018; Kim et al, 2014; Kim, Al Otaiba et al, 2015; Puranik et al, 2008; Wagner et al, 2011). Writing quality is the most widely evaluated dimension of written composition, is arguably the most important dimension, and typically includes coherence and quality of ideas, and use of language (vocabulary and sentence structure; e.g., Coker et al, 2018; Graham et al, 2002; Hooper et al, 2002; Kim et al, 2015; Olinghouse, 2008). Another widely examined dimension is writing productivity , the amount of writing such as number of words and sentences (e.g., Abbott & Berninger, 1993; Berman & Verhoeven, 2002; Kim et al, 2011, 2014; Mackie & Dockrell, 2004; Olinghouse & Graham, 2009; Scott & Windsor, 2000).…”
Section: Direct and Indirect Effects Model Of Writingmentioning
confidence: 99%
“…Their results provide support for a developmental model of writing fluency that is linked to the component skills described in the not-so-simple view of writing. Next, Coker, Ritchey, Uribe-Zarain, and Jennings (2017) identified five profiles of first-grade writers, using latent profile analysis. They found that students in the at-risk profile wrote narratives and descriptions that scored lower on four linguistic measures as compared with students in the average and above-average profiles, suggesting that at-risk students can be identified as early as first grade.…”
Section: Articles In This Issuementioning
confidence: 99%
“…However, only one cognitive measure (orthographic choice) was a significant predictor at all three grade levels. Both of these papers (Coker et al, 2017; Costa et al, 2017) offer productive approaches and yet highlight the complexity of identifying struggling writers early in their schooling. McMaster, Kunkel, Shin, Jung, and Lembke (2017) conducted a rigorous best evidence synthesis on interventions for struggling writers in the primary grades.…”
Section: Articles In This Issuementioning
confidence: 99%